Penerapan Teknologi IOT CNC untuk Peningkatan Kapasitas Produksi Undustri Ukir Samisuko Furnicraft Jepara - Zaenal Arifin (Khaira Ummah, 2023)
Jepara Regency is the center of the carving and furniture industries. The spread of the Jepara carving industry is one of them in the village of Sukosono, Kedung sub-district. The majority of the population's livelihoods are carpenters, furniture craftsmen, and finishing services. Along with the times, there were many factories in Jepara Regency, which had an impact on the lack of carving staff in Jepara. Samisuko Furnicraft is a service partner in this activity. Founded in 2009 by Mr. Muhammad Samiun who is engaged in making calligraphy carvings, door carvings, gebyok carvings, and losters. Problems that exist with Partners: 1) Lack of carving staff. 2) in the production process at the stage of the carving process, the carving staff at the partners have not been able to make carving images with new motifs so that it slows down the production process and acceptance of incoming orders must be limited, 2) Marketing management on the marketplace platform is not optimal. Based on the existing problems, the solutions offered are (1) Socialization and Assistance in the application of CNC MACH technology, (2) Training on marketing with internet marketing. The output of this activity is Publication in the Jawa Pos newspaper on December 23, 2022, Activity Videos will be uploaded on Youtube LPPM UNISNU Jepara and increased partner empowerment starting from increasing production capacity from 400 to 520 pcs, turnover increasing from 20 million to 30 million and assets an increase of 10%.